A política das escolas e a Escola Sem Partido: um estudo sobre ideologias e valores no sistema de ensino de Congonhas - Marcos Paulo Dias Leite Resende (2018)
This research aims to discuss the role of school in the constitution of students political values. School is recognized as an inherently political institution due to its insertion into the social and economic structure of every comunity. The theoretic refference comes from the debate between two different perspectives about schools role. On the one hand are those who support a political neutrality on schools and the institutionalization of mecanisms that inhibit teachers political expressions in classroom. The positivist approach and conservative moviments that support the tradicional educational model are attached to this perspective especially the supporters of Movimento Escola sem Partido (School without Party Moviment). On the other hand are those who support an educational model guided by the goal of fostering in students the capacity of stablish a critical view about society and schools contents. This approach not only believes to be natural that school can be politically positioned, but also promote a debate inside the educational enviroment. Therefore, the mainly goal of this research is to iddentify the predominant values of political and educational agents of Congonhas Municipal Educational System. I conducted an interview with managers of Municipal Secretariat of Education, school directors and teachers. The content was analysed by a Critical Discourse Analysis approach.